Characteristics of Plasmacytoid Dendritic Cell and CD4+ T Cell in HIV Elite Controllers - Jean-Philippe Herbeuval; Nikaïa Smith; Jacques Thèze (Clinical and Developmental Immunology)
Despite variability, the majority of HIV-1-infected individuals progress to AIDS characterized by high viral load and massive CD4+ T-cell depletion. However, there is a subset of HIV-1-positive individuals that does not progress and spontaneously maintains an undetectable viral load. This infrequent patient population is defined as HIV-1 controllers (HIV controllers), and represents less than 1% of HIV-1-infected patients. HIV-1-specific CD4+ T cells and the pool of central memory CD4+ T cells are also preserved despite immune activation due to HIV-1 infection. The majority of HIV controllers are also defined by the absence of massive CD4+ T-cell depletion, even after 10 years of infection. However, the mechanisms involved in protection against HIV-1 disease progression have not been elucidated yet. Controllers represent a heterogeneous population; we describe in this paper some common characteristics concerning innate immune response and CD4+ T cells of HIV controllers.